Implementasi Kebijakan Pencegahan dan Penanganan Tindak Pidana Perdagangan Orang (TPPO): (Studi Pekerja Imigran di Kota Kupang Nusa Tenggara Timur) - Anasthasya Tri Syafianingrum; David B. W. Pandie; Made N. D. Andayana; Alfred O. Ena Mau (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the implementation of policies for the prevention and handling of trafficking in Kupang City based on Kupang City Regional Regulation Number 3 of 2019. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation at the Indonesian Migrant Worker Protection Service Center (BP3MI) of NTT Province and the Directorate of Criminal Investigation for the Protection of Women and Children and the Eradication of Trafficking in Persons (Ditreskrim PPA and PPO) of the NTT Police. Data analysis used the Miles and Huberman interactive model. This study uses the Integrated Model (Diori, 2021) which emphasizes six variables of policy implementation, namely leadership, organizational structure, clarity of policy objectives, task assignment, resource use, and commitment of field implementers. The results of the study show that the implementation of the TPPO policy in Kupang City has been running operationally through cross-agency coordination, but it has not been structurally optimal due to budget limitations, weak local government commitments, and socio-cultural factors of the community that affect the law enforcement process. This research emphasizes the importance of integrating trafficking policies in regional development planning and strengthening cross-sector collaboration to increase the effectiveness of preventing and handling trafficking in persons.